Pengaruh Emosi Terhadap Efektivitas Komunikasi Interpersonal - Wijaya, Yeny Duriana; Larasati, Ayu (Syntax Corporation, 2025)
This study aims to analyze how emotions affect the effectiveness of interpersonal communication in various social contexts. Emotions such as anger, sadness, happiness, and anxiety can be an obstacle or support in the communication process. With qualitative methods in the form of literature studies and in-depth interviews, it was found that good emotion management increases the effectiveness of message delivery and strengthens interpersonal relationships. The implications of this research are important for the development of communication skills in both professional and personal contexts